2011
DOI: 10.1002/chem.201101373
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Elimination of ArCF3 from Bidentate PdII Complexes: A Computational Study

Abstract: The reductive eliminations of ArCF(3) from Pd(II) complexes bearing small- and large-bite-angle phosphane ligands have been investigated using computational methods. QM/QM' and QM/MM studies were applied and complemented with CP2K molecular dynamics investigations. The ligand substituents were varied and a decomposition analysis was performed to allow us to gain insights into the steric and electronic properties of the ligands. The greater reactivity of Xantphos-derived (Xantphos=4,5-bis(diphenylphosphino)-9,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 210 publications
4
43
0
Order By: Relevance
“…237 A computational study from 2011 by Anstaett and Schoenebeck using the ONIOM B3LYP/6-31+G(d,p) (LANL2DZ):HF/LANL2MB methodology explained that the origin of this superior reactivity stems from the greater destabilization of the reactant complex relative to the transition state, which overall lowers the barrier of reductive elimination from 33.9 kcal/mol in the case of dppe to 25.7 kcal/ mol for Xantphos ( Figure 13). 238 In 2012, similar results were also obtained by Macgregor, Grushin, and co-workers when studying the Xantphos system. A good agreement between the experimentally measured barrier of ΔH ‡ = 25.9 kcal/mol and a predicted barrier of ΔH ‡ calc = 24.8 kcal/mol and ΔG ‡ calc = 25.0 kcal/mol (at the B97D/6-31G(d,p) (SDD) level of theory) was reached.…”
Section: Aryl Trifluoromethylationsupporting
confidence: 87%
“…237 A computational study from 2011 by Anstaett and Schoenebeck using the ONIOM B3LYP/6-31+G(d,p) (LANL2DZ):HF/LANL2MB methodology explained that the origin of this superior reactivity stems from the greater destabilization of the reactant complex relative to the transition state, which overall lowers the barrier of reductive elimination from 33.9 kcal/mol in the case of dppe to 25.7 kcal/ mol for Xantphos ( Figure 13). 238 In 2012, similar results were also obtained by Macgregor, Grushin, and co-workers when studying the Xantphos system. A good agreement between the experimentally measured barrier of ΔH ‡ = 25.9 kcal/mol and a predicted barrier of ΔH ‡ calc = 24.8 kcal/mol and ΔG ‡ calc = 25.0 kcal/mol (at the B97D/6-31G(d,p) (SDD) level of theory) was reached.…”
Section: Aryl Trifluoromethylationsupporting
confidence: 87%
“…On first sight and in agreement with general organometallic reactivity guidelines, the large bite angle of Xantphos facilitated the transformation, with dppe having a smaller angle being unable to mediate reductive elimination. Computational studies performed in our group, in which we altered the substituent from phenyl to H in these ligands—a modification easily studied computationally but very challenging to study experimentally—suggested that the barriers are not actually correlated with the bite angle, but the interaction of the substituents at the phosphine center with the aryl and trifluoromethyl groups was crucial 36. For small‐bite‐angle ligands, such as dppe, the destabilization of the transition state was more pronounced than the reactant complex, making reductive elimination less favored.…”
Section: Case Study 3: Use Of Computation Before Experiments For Desigmentioning
confidence: 99%
“…In benzene solution the compound exists as a 10:1 mixture of the cis and trans isomers, whereas in more polar solvents (thf, CH 2 Cl 2 ) only the cis isomer was observed. [68] Buchwald and coworkers investigated the palladium-catalyzed trifluoromethylation of different aryl and heteroaryl chlorides, which exhibits compatibility with a wide variety of functional groups. The compound was found to undergo a clean Ph-CF 3 reductive elimination in benzene at 80°C in 3 h in the presence of free Xantphos (1:1) with ca.…”
Section: 1b Palladium Derivativesmentioning
confidence: 99%